Subthreshold Micropulse Laser (577 nm) Therapy with an Individual Approach for Power Titration in Patients with Chronic Central Serous Chorioretinopathy (Pilot Study) - Taras Kustryn; Oleg Zadorozhnyy; Illia Nasinnyk; Nataliya Pasyechnikova; Andrii Korol (Journal of Ophthalmology)
Purpose. To study the safety and effectiveness of subthreshold micropulse (SML) 577 nm laser therapy with an individual power titration in treating patients with chronic central serous chorioretinopathy (CSC). Methods. The study was a prospective, single-centre observation of 30 patients (30 eyes) with chronic CSC. All patients with chronic CSC were treated with a 577 nm micropulse laser. Individual power parameters for each patient were titrated in a micropulse mode. The primary outcome measure was best-corrected visual acuity (BCVA) at 6-month follow-up. The secondary outcome measures were as follows: central retinal thickness (CRT) and maximum subretinal fluid height (SRFH) according to optical coherence tomography, number of laser sessions, and treatment safety at 6-month follow-up. Results. Before treatment, the mean BCVA was 0.35 ± 0.16, the mean CRT was 285 ± 76 µm, and the mean SRFH was 311 ± 85 µm. Six months after 577 nm SML therapy, there was a statistically significant increase in the mean BCVA with the maximum correction to 0.45 ± 0.15 (p=0.001). The mean CRT and SRFH decreased significantly to 236 ± 45 μm (p=0.003) and 45 ± 25 μm (p=0.001), respectively. At the end of the follow-up, complete resorption of the subretinal fluid was noted in 50% (15 eyes), and in 43% (13 eyes), a decrease in the SRFH was observed. During the entire observation period, 25 patients underwent 1 session of 577 nm SML therapy, 2 patients underwent 2 sessions, and 3 patients underwent the intervention three times. Conclusion. SML 577 nm therapy with individual selection of laser power in a micropulse mode is a safe and effective method of treating patients with chronic CSC. Further studies are needed to test the long-term safety and efficacy of 577 nm SML therapy with individual power settings in chronic CSC.